O impacto dos investimentos em P&D nos esforços de inovação em pequenas e médias empresas na américa latina - Santos, Anderson Freitas dos (2022)
Latin America is a large territory, holding great relevance in the global economy, especially because of the vast diversity and concentration capacity of natural resources. However, it presents a complex environment for economic development, due to historical, political, and geopolitical characteristics. Alternatively, entrepreneurship, represented by small and medium-sized enterprises (SMEs), provides the opportunity to accelerate general development, projecting greater integration with the global economy, with the growing the internationalization of these companies. Likewise, strengthening innovation efforts and investments in research and development (R&D) are essential mechanisms in this construction. This study examined the influence of R&D investments in innovation efforts in SMEs in Latin America, besides the effect that internationalization efforts provide in this relationship. The methodology employed involves: (a) quantitative research, based on the World Bank’s database, specifically regarding data from the Enterprise Survey; (b) factor analysis and regressive analysis of the collected data. This study contributed for the understanding of the Innovation Efforts of SMEs in Latin America, and to statistically measure that R&D investments and internationalization efforts have a positive and significant influence on innovation efforts that allow Latin American SMEs to increase their competitiveness through the improvement of products/services or processes. In this study, the three initial hypotheses were statistically confirmed. Thus, we found that R&D investments positively influence innovation efforts and that companies that invest in R&D and additionally employ internationalization efforts are more likely to present innovation efforts.